Efficacy of CPX‐351, (cytarabine:daunorubicin) liposome injection, against acute lymphoblastic leukemia (ALL) xenograft models of the Pediatric Preclinical Testing Program. Issue 1 (9th September 2014) - Carol, Hernan; Fan, Mannie M. Y.; Harasym, Troy O.; Boehm, Ingrid; Mayer, Lawrence D.; Houghton, Peter; Smith, Malcolm A.; Lock, Richard B.
ABSTRACT Background CPX‐351, a liposomal formulation of cytarabine and daunorubicin co‐encapsulated at an optimized synergistic 5:1 molar ratio, has demonstrated improved clinical outcomes over conventional cytarabine/daunorubicin treatment in a randomized phase 2 trial in patients with AML as well as superior efficacy against preclinical leukemia models when compared to the free drugs in combination. Procedures Given the promising phase 2 data, limited toxicities observed, and the known clinical activities of cytarabine/daunorubicin, we assessed the efficacy of CPX‐351 against a panel of childhood ALL xenograft models. Plasma pharmacokinetics of cytarabine and daunorubicin following CPX‐351 treatment were determined by HPLC in order to correlate efficacy with drug exposure. Results CPX‐351, at a dose of 5 units/kg (corresponding to 5 mg/kg cytarabine and 2.2 mg/kg daunorubicin), was highly efficacious against all xenografts tested, inducing complete responses in four B‐lineage xenografts and partial response in one T‐lineage xenograft. These therapeutic responses were achieved with CPX‐351 doses that provided drug exposures (based on Cmax and AUC) comparable to those observed in patients with AML. Conclusions These results suggest that CPX‐351 may be a promising chemotherapeutic to be utilized in the treatment of ALL and support its testing in pediatric patients with leukemia. Pediatr Blood Cancer 2015;62:65–71. © 2014 Wiley Periodicals, Inc.